Paenibacillus spp infection among infants with postinfectious hydrocephalus in Uganda: an observational case-control study - Morton, Sarah U; Hehnly, Christine; Burgoine, Kathy; Ssentongo, Paddy; Ericson, Jessica E; Kumar, M Senthil; Hagmann, Cornelia; Fronterre, Claudio; Smith, Jasmine; Movassagh, Mercedeh; Streck, Nicholas; Bebell, Lisa M; et al. (The Lancet Microbe, 2023)
Background: Paenibacillus thiaminolyticus is a cause of postinfectious hydrocephalus among Ugandan infants. To determine whether Paenibacillus spp is a pathogen in neonatal sepsis, meningitis, and postinfectious hydrocephalus, we aimed to complete three separate studies of Ugandan infants. The first study was on peripartum prevalence of Paenibacillus in mother–newborn pairs. The second study assessed Paenibacillus in blood and cerebrospinal fluid (CSF) from neonates with sepsis. The third study assessed Paenibacillus in CSF from infants with hydrocephalus. Methods: In this observational study, we recruited mother–newborn pairs with and without maternal fever (mother– newborn cohort), neonates (aged ≤28 days) with sepsis (sepsis cohort), and infants (aged ≤90 days) with hydrocephalus with and without a history of neonatal sepsis and meningitis (hydrocephalus cohort) from three hospitals in Uganda between Jan 13, 2016 and Oct 2, 2019. We collected maternal blood, vaginal swabs, and placental samples and the cord from the mother–newborn pairs, and blood and CSF from neonates and infants. Bacterial content of infant CSF was characterised by 16S rDNA sequencing. We analysed all samples using quantitative PCR (qPCR) targeting either the Paenibacillus genus or Paenibacillus thiaminolyticus spp. We collected cranial ultrasound and computed tomography images in the subset of participants represented in more than one cohort. Findings: No Paenibacillus spp were detected in vaginal, maternal blood, placental, or cord blood specimens from the mother–newborn cohort by qPCR. Paenibacillus spp was detected in 6% (37 of 631 neonates) in the sepsis cohort and, of these, 14% (5 of 37 neonates) developed postinfectious hydrocephalus. Paenibacillus was the most enriched bacterial genera in postinfectious hydrocephalus CSF (91 [44%] of 209 patients) from the hydrocephalus cohort, with 16S showing 94% accuracy when validated by qPCR. Imaging showed progression from Paenibacillus spp-related meningitis to postinfectious hydrocephalus over 1–3 months. Patients with postinfectious hydrocephalus with Paenibacillus spp infections were geographically clustered. Interpretation: Paenibacillus spp causes neonatal sepsis and meningitis in Uganda and is the dominant cause of subsequent postinfectious hydrocephalus. There was no evidence of transplacental transmission, and geographical evidence was consistent with an environmental source of neonatal infection. Further work is needed to identify routes of infection and optimise treatment of neonatal Paenibacillus spp infection to lessen the burden of morbidity and mortality.
Keywords: Paenibacillus spp infection; Uganda; Children; Meningitis; Postinfectious hydrocephalus